Temple University Aegean Symposium: A Compendium - Betancourt, Philip P. (INSTAP Academic Press, 2015)
Intro -- Preface, by Philip P. Betancourt -- The Possible Role of Tomb Robbers and Viziers of the Eighteenth Dynasty inConfusing Minoan Chronology, by Leon Pomerance. -- Metal Inlaying in Minoan and Mycenaean Art, by Ellen N. Davis -- Radiocarbon Dates from Akrotiri on Thera, by Henry N. Michael -- The Ox-hide Ingots and the Development of Copper Metallurgy in the Late Bronze Age,by James D. Muhly -- Economic Implications of the Reed Painter's Vases, by Philip P. Betancourt -- Some Faience, Blue Frit, and Glass from Fifteenth Century Knossos,by Gerald Cadogan -- On Theoretical Principles in Aegean Bronze Age Mural Restoration,by M.A.S. Cameron -- SITE SURVEY Aegean Settlements and Transhumance, by L. Vance Watrous -- ARCHAEOLOGICAL EXCAVATION Some Unpublished Mycenaean Pottery from Sarepta, by Robert Koehl -- PHYSICAL ANTHROPOLOGY The People of Kato Zakro, by M.J. Becker -- PHILOLOGY DA and TA as Premisses for Rational Arguments, by Emmett L. Bennett, Jr -- ART HISTORY Perspective and the Third Dimension in Theran Painting, by Philip P. Betancourt -- METALLURGY The Ancient Tin Trade in the Eastern Mediterranean and Near East,by Tamara S. Wheeler -- RADIOCARBON DATING New Radiocarbon Dates from Akrotiri, Thera, by H.N. Michael and G.A. Weinstein -- HISTORICAL INTERPRETATION Aegean Leisure, by Claireve Grandjouan -- The Mount Holyoke Collection of Minoan Pottery, by Karen Polinger Foster -- The LM IB Painted Pottery of Eastern Crete, by Jean Silverman -- Obsidian from Crete: Problems in Lithic Analysis, by Nicholas Hartmann -- Thoughts on Prehistoric Potters and Ceramic Change, by Karen D. Vitelli -- A Bronze Pivot Shoe from the Residential Building of Gla, by Sp. Iakovides -- Excavations at Kommos (1977), by Joseph W. Shaw -- A Plea for the Abandonment of the Term "Submycenaean", by Jeremy B. Rutter -- Introduction, by Philip P. Betancourt.